Motivasi Siswa Sekolah Dasar dalam Mempelajari Bahasa Arab: Tinjauan Psikologi belajar Anak - Nur Muh Muhammad (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2018)
Students’ motivation in learning Arabic language in children learning psychology review. Muhammadiyah Pakem Elementary School is one of school that use Arabic Language in the curriculum from the first grade to the sixth grade. The students in elementary school have unique characteristics of the secondary school or senior high school, because elementary school will be the end of the children (golden) age. Therefore, it is very important to know what motivations and characteristics of this age. The aim of this research is to know the best (appropriate) method or technique in learning by knowing students’ motivation. This research used qualitative method in data analizing. The result of this research was motivation from others (extrinsic) reached 72,2% and motivation from the students themself (intrinsic) reached 16%. And the demotivating factors of the students were the lack of preparation by the students to learn and the difficulty of Arabic language materials for the students.